The awareness of faculty members at Prince Sattam bin Abdulaziz University of the use of the e-learning platform in light of the outbreak of the COVID 19 virus and their attitudes towards inquiry-based learning - El-Gohary, Hala Khairy Abdel-Ghany (Journal of Educational and Psychological Sciences, 2020)
This study aimed to measure the awareness of faculty members at Prince Sattam bin Abdulaziz University of the use of the e-learning platform in light of the outbreak of the COVID 19 virus and their attitudes towards inquiry-based learning. The researcher used the descriptive approach, semi-experimental, and statistical demographic variables to suit her for the purposes of the study. The study sample consisted of (100) members of the teaching staff of Prince Sattam bin Abdulaziz University, who were chosen in a stratified random manner.The researcher calculated the stability coefficient of the internal consistency of the questionnaire with its four dimensions and calculated the coefficient of internal consistency of the other questionnaire in its three dimensions. The researcher also used the statistical demographic variables prepared by the Deanship of Information Technology at Prince Sattam bin Abdulaziz University during the period of suspension of the study.The most important results of the study were as follows: The degree of awareness of faculty members at Prince Sattam bin Abdulaziz University on the e-learning platform "BlackBoard" on the overall questionnaire was high, with an average score of (3,41) and the attitudes of the faculty members at Prince Sattam University in the Kingdom of Saudi Arabia towards inquiry-based learning environment were high, with a mean (3.65), because the survey strategy is an educational process that allows students to use survey skills and support self-learning skills that are To satisfy curiosity, organize knowledge and generate ideas.Recommendations: Searching for obstacles and setting appropriate solutions for them to achieve goals and quality in the educational process via the Internet (Blackboard(, and Developing the skills of faculty members and students alike via the Internet (Blackboard). &Emphasizing the professional development of a faculty member via the Internet (BlackBoard). Finally Encouraging online inquiry-based learning environment (Blackboard).
Keywords: E-learning platform; COVID 19; Survey Learning